Optimization of Patrol by the Samapta Batang Police to Prevent the Crime of Motor Vehicle Theft - Sinuhaji, Vany Patricia Thesaura (Advances in Police Science Research Journal, 2024)
The Covid-19 pandemic has succeeded in bringing the increasement of the unemployment rate as a result of global economic slowdown resulting in termination of employment  and a decrease in the creation of job opportunities in Indonesia, one of wich is in Batang Regency. In 2019 there was a surge in the number of unemployment rate in Batang Regency by 72.1% from 16,755 to 28,835 people. This surge brought new problems to society such as the increasement of crime rate caused by human inabiliity to meet primary needs and look for shortcuts with the intention of earning income. One of shortcuts is by committing a crime of motor vehicle theft. In accordance with Law Number 2 of 2002 concerning the Indonesian National Police, the Batang Police has made pre-emptive, preventive, and repressive efforts to reduce the number of motor vehicle thefts. These efforts have not been carried out effectively, so that improvement is needed, especially in preventive efforts, namely the implementation of two-wheeled patrols which are carried out as the backbone of the National Police in preventing disruption to security and order. The author's goal in raising this issue is to analyze the implementation of the Samapta Police Unit's two-wheeled patrols to prevent criminal acts of motorized vehicle theft which have been running so far. This research uses a qualitative approach with the type of field research and collects data through interviews, observation, and document studies. The conclutions are that the Turjawali Unit of the Samapta Unit of the Batang Police must optimize the implementation of patrols by adjusting patrols to vulnerable conditions, improving the quality of patrols, and maximizing all available resources. In addition, two-wheeled patrol officers are expected to be able to increase the contribution of the community as the eyes and ears of the National Police to prevent motorized vehicle crimes.